Surgical clipping is still a good choice for the treatment of paraclinoid aneurysms - Felix Hendrik Pahl; Matheus Fernandes de Oliveira; Roger Schmidt Brock; José Erasmo Dal Col Lucio; José Marcus Rotta (Arquivos de Neuro-Psiquiatria)
ABSTRACT Paraclinoid aneurysms are lesions located adjacent to the clinoid and ophthalmic segments of the internal carotid artery. In recent years, flow diverter stents have been introduced as a better endovascular technique for treatment of these aneurysms. Method From 2009 to 2014, a total of 43 paraclinoid aneurysms in 43 patients were surgically clipped. We retrospectively reviewed the records of these patients to analyze clinical outcomes. Results Twenty-six aneurysms (60.5%) were ophthalmic artery aneurysms, while 17 were superior hypophyseal artery aneurysms (39.5%). The extradural approach to the clinoid process was used to clip these aneurysms. One hundred percent of aneurysms were clipped (complete exclusion in 100% on follow-up angiography). The length of follow-up ranged from 1 to 60 months (mean, 29.82 months). Conclusion Surgical clipping continues to be a good option for the treatment of paraclinoid aneurysms.